Kinetic Comparison Of Lignin Removal From Sugarcane (Saccharum Officinarum) And Cactus (Opuntia Ficus-Indica) Bagasse By Using Laccase Enzyme - Cardona López, Nubia Rosa; Marín, James Alberto; Medina Vargas, Óscar Julio; Ríos, Luis Alberto; Caicedo Pineda, Gerardo Andrés (Ciencia En Desarrollo, 2021)
The present study focused to evaluate the effect of a laccase from Aspergillus sp. in order to expose cellulose contained in both sugarcane (Saccharum officinarum, BCA) and Opuntia-ficus cactus (BOF) bagasses. The kinetic parameters of the enzymatic activity were calculated for each of the materials, using the initial rates method at various bagasse:solution ratios (10 g:L to 50 g:L) and a total reaction time of 1 h. The assays presented a non-enzymatic removal of extractables by the buffer effect, under the evaluated reaction conditions. On the other hand, there was no dissolution of cellulose or hemicellulose, but there was lignin. Therefore, the results were analyzed, considering the Michaelis-Menten equation and using the disappearance rate of the glignin:L ratio as a basis. Through a Lineweaver-Burk linearization, the best fit of the values was obtained, where Vmax = 14.9566 glignina:L and Km = 40.2011 glignina:L/h for BCA assays (R = 0.9933) and Vmax = 26.8300 glignina:L and Km = 43.5575 glignina:L/h for BOF assays (R = 0.9972). Based on the above, although laccase presented a similar enzymatic affinity for both bagasses, a better catalytic efficiency is predicted towards lignin removal from BOF (0.6160).